2020
DOI: 10.1021/jacs.0c06360
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide Self-Assembly Modulated by Glycan Stereochemistry through Glycan–Aromatic Interactions

Abstract: Carbohydrates are often utilized to provide hydrophilicity and hydroxyl-based hydrogen bonds in self-assembling glycopeptides, affording versatile scaffolds with wide applicability in biomedical research. However, how stereochemistry of carbohydrates impacts the self-assembly process remains unclear.Here we have established a dimeric tyrosine-rich glycopeptide system for probing the corresponding hydrogelating behavior under the influence of site-and stereospecific glycosylations. Comparison of 18 glycoforms b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…As shown in Figure 3 Ai, GlcN-NPmoc produced nanofiber networks, which is characteristic of supramolecular hydrogels. 1 , 7 , 10 Meanwhile, GalN-NPmoc formed non-networked spherical structures, as seen in Figure 3 Aii. This obvious morphological difference is consistent with their distinct hydrogel formation ability.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As shown in Figure 3 Ai, GlcN-NPmoc produced nanofiber networks, which is characteristic of supramolecular hydrogels. 1 , 7 , 10 Meanwhile, GalN-NPmoc formed non-networked spherical structures, as seen in Figure 3 Aii. This obvious morphological difference is consistent with their distinct hydrogel formation ability.…”
Section: Resultsmentioning
confidence: 96%
“…For the design of self-assembling molecules including supramolecular hydrogelators, carbohydrates are attractive not only because of the presence of multiple hydrophilic hydroxyl groups to modulate the amphiphilic tendency but also their inherent chirality, which facilitates the asymmetric arrangement of the self-assembling molecules to form fibrous supramolecular nanoarchitectures suitable for hydrogel formation. , In particular, amino sugars including galactosamine (GalNH 2 , 2-amino-2-deoxy- d -galactose) and glucosamine (GlcNH 2 , 2-amino-2-deoxy- d -glucose), which are major components of structural polysaccharides present on the surface of mammalian cells, are useful because they possess a single amino group at the C2 position that serves as an anchor site for the simple and selective conjugation with a variety of functionalities conducive to the self-assembly behavior, including aromatic amino acids and alkyl chains . For instance, Birchall et al recently reported simple supramolecular hydrogelators derived from amino sugars bearing the fluorenyl-9-methoxycarbonyl (Fmoc) group as a powerful self-assembly facilitating group (referred to as GalN- and GlcN-Fmoc in Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the atomic-level structure of sequence-defined synthetic polymers is critical for the design of self-assembled hierarchical materials, a variety of the state-of-the-art characterization techniques, including in situ AFM and Cryo-TEM (c.f., section ) have been frequently used toward this purpose. However, despite tremendous efforts that have been made to characterize the structures of these sequences and their self-assembled materials, it is still a grand challenge to obtain atomic-level structural information. , One way to address such a challenge is to obtain 3D crystals that are large enough for single-crystal X-ray crystallography, , because the atomic-level crystal structures obtained from this technique provide unprecedented insights into the interactions required to organize sequence-defined assemblers into hierarchical materials. Therefore, obtaining 3D single crystals suitable for single-crystal X-ray crystallography has become a promising way to advance our understanding of peptoid self-assembly into hierarchical materials . In this section, two types of peptoid-based 3D single crystals are discussed based on their main formation driving forces, including metal–peptoid coordination and peptoid–peptoid interactions.…”
Section: Hierarchical Self-assembly Of Sequence-defined Synthetic Pol...mentioning
confidence: 99%
“…During the past decade, remarkable effort has been devoted to the synthesis of glyco-polypeptides and their self-assembly behaviors for the biomimicry of native ones and the development of bioinspired functional materials. , Especially, tremendous achievements have been made in the construction of glyco-polypeptide-based nanostructures via self-assembly in aqueous solution . Notably, the carbohydrates on the peptides not only make an inherent contribution to the bioavailability but also effectively and uniquely tune the folding and aggregate behavior of peptide skeletons by the saccharide stereochemistry and glycan–aromatic interactions . However, among the elegant reported cases, most of the architectures of glyco-polypeptides were focusing on the linear or linear-branched building blocks, which commonly formed zero-dimensional structures such as micelles and vesicles. Until date, there are limited reports about the synthesis and self-assembly of native-like glyco-polypeptides with various and complex architectures.…”
Section: Introductionmentioning
confidence: 99%
“…23 Notably, the carbohydrates on the peptides not only make an inherent contribution to the bioavailability but also effectively and uniquely tune the folding and aggregate behavior of peptide skeletons by the saccharide stereochemistry and glycan−aromatic interactions. 24 However, among the elegant reported cases, most of the architectures of glyco-polypeptides were focusing on the linear or linear-branched building blocks, which commonly formed zero-dimensional structures such as micelles and vesicles. 25−28 Until date, there are limited reports about the synthesis and self-assembly of native-like glyco-polypeptides with various and complex architectures.…”
Section: ■ Introductionmentioning
confidence: 99%